DOI: 10.47749/t/unicamp.2006.386195
|View full text |Cite
|
Sign up to set email alerts
|

O ensino de geologia como instrumento formador de uma cultura de sustentabilidade

Abstract: Título em inglês: Geology education as na instrument for a culture of sustainability: the Geoschool Project in São Jose do Rio PretO, SP ..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
3
0
7
Order By: Relevance
“…The modules that focused on the regions of São José do Rio Preto, Cajamar and Monte Mor were more restricted in terms of interaction with teachers from these municipalities, with little or no participation from neighboring cities. Each module has developed, applied and tested experimental didactic materials composed of geological data, images and maps, which were generated from fieldwork, bibliographic and laboratory studies (BARBOSA, 2013;PIRANHA, 2006;PIRANHA;CARNEIRO, 2006CARNEIRO, , 2009. Interdisciplinary themes like environment, terrestrial dynamics, nature cycles, available resources (energy, water, soils, and mineral goods) were the main focus, in addition to more comprehensive concepts, such as water and rock cycles.…”
Section: A Summary Of the Project Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modules that focused on the regions of São José do Rio Preto, Cajamar and Monte Mor were more restricted in terms of interaction with teachers from these municipalities, with little or no participation from neighboring cities. Each module has developed, applied and tested experimental didactic materials composed of geological data, images and maps, which were generated from fieldwork, bibliographic and laboratory studies (BARBOSA, 2013;PIRANHA, 2006;PIRANHA;CARNEIRO, 2006CARNEIRO, , 2009. Interdisciplinary themes like environment, terrestrial dynamics, nature cycles, available resources (energy, water, soils, and mineral goods) were the main focus, in addition to more comprehensive concepts, such as water and rock cycles.…”
Section: A Summary Of the Project Goalsmentioning
confidence: 99%
“…The large volume of instructional materials produced in SJRP resulted from contact with teachers in the municipality that exceeded expectations (PIRANHA, 2006). The Cajamar module revealed that local educational managers have poor success rates after efforts with first graders to promote a positive image of the municipality and its history, which is marked by mining.…”
Section: Some Achievements Of the Geo-school Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura sobre o ensino de temas geocientíficos mostra o quanto são elaboradas pesquisas dedicadas a investigar a importância desses conteúdos na Educação Básica brasileira, demarcando os contributos dos temas geocientíficos para as demais Ciências, bem como as práticas pedagógicas de ensino que tornam essa aprendizagem mais significativa e mais representativa no universo de vivência do educando (ASSARF; ORION, 2005;BACCI, 2015;ALMEIDA, 2004;COMPIANI, 1996;FIRMINO;BARBOSA;RODRIGUES, 2019;GONÇALVES;SICCA, 2018;GUIMARÃES, 2004;KASTENS;AGRAWAL;LIBEN, 2009;LACREU, 2007;CARNEIRO, 2009;PONTE;PIRANHA, 2020).…”
Section: Introductionunclassified
“…Bem como da responsabilidade social do Estado em propiciar o efetivo diálogo entre os diferentes atores envolvidos no processo de licenciamento, cujo acesso à informação ambiental organizada e responsável, é peça fundamental. A questão do acesso à informação como requisito básico para a promoção da cidadania e para a formação de uma "consciência ambiental" visando reverter o caminho da degradação ambiental no Planeta, não é assunto novo e considerado aqui como um consenso, uma luta coletiva já sedimentada em prol da educação e para o meio ambiente (QUINTAS, 2004;JACOBI, 2003JACOBI, , 2005PIRANHA & CARNEIRO, 2009;LOUREIRO, 2010).…”
Section: Introductionunclassified